Amyloidosis of the aortic valve in patients with degenerative and bicuspid aortic stenosis. (3rd October 2022) - Perez, E; Abedat, S; Meir, K; Pollak, A; Shapira, O; Erez, E; Leibowitz, D; Asleh, R; Amir, O; Beeri, R
Abstract: Introduction: Aortic stenosis (AS) is a common valvular disease, resulting in substantial morbidity and mortality. In younger patients, AS may occur as part of the bicuspid aortic valve (BAV) syndrome. Transthyretin cardiac amyloidosis (ATTR-CA) is an infiltrative disorder caused by the extracellular deposition of insoluble amyloid-derived fibrils. Recent studies have shown the presence of ATTR-CA in 4%-29% of degenerative AS patients. We hypothesized that amyloidosis may be involved in valve injury leading to AS. Material and methods: We studied the aortic valves of 124 patients who underwent surgical aortic valve replacement at our institution over the last decade, included in our cardiosurgical database. Valves from 86 degenerative AS patients were compared to a control group of 38 patients with BAV stenosis. Patients with pure aortic regurgitation, history of rheumatic disease, or severe renal disease were excluded. The slides were stained with Congo red, and Thioflavin S then examined with regular, fluorescence and polarized light microscopy. Results: In the degenerative AS group, Congo red and Thioflavin S staining was positive in 63% of the valves and 37% negative. The bicuspid AS group showed 68% positive and 32% negative for the Congo Red and Thioflavin S stains. Discussion and conclusion: Our results indicate the presence of valvular amyloidosis in patients with AS, whether due to degenerative or congenital etiologies. This corroborates several recent studies. Intriguingly, there was an equally positive Congo red and Thioflavin S signal in bicuspid aortic valves. We speculate that the positive staining in the BAV group may indicate an inflammatory process associated with valve pathology inducing the accumulation of amyloid, and thus may not be transthyretin, as we expect in the experimental group. Another explanation may be that amyloidosis may be an epiphenomenon of valve "wear and tear" and not related to the pathogenesis in either etiology. Specific TTR immunofluorescence is underway to elucidate this question. Funding Acknowledgement: Type of funding sources: None.